Characterisation of TNF block haplotypes affecting the production of TNF and LTA - Tan, J.; Temple, S.; Kee, C.; Waterer, G.; Tan, C.; Gut, I.; Price, Patricia (Blackwell Munksgaard, 2011)
Polymorphisms in the central major histocompatibility complex (MHC) (particularly TNF and adjacent genes) associate with several immunopathological diseases and with susceptibility to pneumonia. The MHC is characterised by strong linkage disequilibrium (LD), so identification of loci affecting disease must be based on haplotypes. We have defined 31 tumour necrosis factor (TNF) block haplotypes (denoted FV1-31) in Caucasians, Asians and Australian Aboriginals. This study correlates the carriage of TNF block haplotypes with TNF and lymphotoxin alpha (LTA) protein production by peripheral blood mononuclear cells from 205 healthy Caucasian subjects, following in vitro stimulation with Streptococcus pneumoniae (S. pneumoniae; gram-positive bacteria), Escherichia coli (E. coli; gram-negative bacteria) or TNF over 4, 8 and 24 h. Fifteen haplotypes were present at > 1%, accounting for 94.5% of the cohort. The haplotypes were grouped into five families based on common alleles. Following stimulation, cells from carriers of the FV10 haplotype (family 2) produced less LTA compared with non-FV10 carriers. Carriers of the FV18 haplotype (family 4) produced more LTA than other donors. Induction of TNF by S. pneumoniae following 24 h stimulation was also greater in donors with FV18. The FV18 haplotype associated with the 44.1 MHC ancestral haplotype (HLA-A2, -C5, -B44, -DRB1*0401 and -DQB1*0301) that has few disease associations. FV16 occurred in the 8.1 MHC haplotype (HLA-A2, B8, DR3) that is associated with multiple immunopathological diseases. FV16 did not affect TNF or LTA levels. The findings suggest that many genetic variations critical in vivo are not effectively modelled by short-term cultures. © 2010 John Wiley & Sons A/S.